Hubungan Kadar Kalium dan Kadar Ureum Terhadap Jenis Obat Baru pada Pasien Tuberkulosis Resistan Obat (TB RO) - Anggita, Sasha Marwah; Qomariyah, Nurul; Kahar, Fitriani (Poltekkes Kemenkes Semarang, 2024)
The use of new types of drugs in RO TB patients will cause disturbances in the body's electrolytes, especially potassium levels, as well as disturbances in urea levels caused by the excretion of urea that is retained in the body. Continuous increases in urea in the body result in the kidneys not being able to work optimally. The aim of this study was to determine the relationship between potassium levels and urea levels on new types of drugs in RO TB patients. The research method used is analytical observational with a cross sectional approach. This research was conducted on 16 February – 16 March 2023 with research subjects being RO TB patients who received treatment with a new type of drug at the Lung Hospital dr. Ario Wirawan Salatiga as many as 21 respondents using a sampling technique that is the total population. Potassium levels were measured using the ISE (Ion Selective Electrode) method and urea levels used the enzymatic UV test method. The data was then processed using the Shapiro-Wilk normality test, then continued with prerequisite tests (crosstab test and homogeneity test) then continued with hypothesis testing, because my data scale was ratio and nominal, the alternative test used was the Chi-Square Test. The equipment test results obtained a homogeneity test with a P value of 0.698 and 0.610 (>0.05), meaning the data was homogeneous. The test results for the relationship between potassium and urea levels on new types of drugs for RO TB patients were Chi-Square hypothesis test results with a P value of 0.152 and 0.384 (> 0.05) means there is no relationship between potassium levels and urea levels on new types of drugs in RO TB patients. The results show that the TB drugs bedaquiline and delamanid do not cause kidney function disorders so that RO TB patients can consume these TB drugs regularly.